« Encore de gauche… malgré tout » - Éric Agrikoliansky; Philippe Aldrin; Sandrine Lévêque (La Nouvelle Revue du Travail)
Based on repeated interviews with public primary school teachers who identified as “left-wing” during the 2022 presidential campaign, this article investigates the mechanisms underpinning their politicized attachment to their profession. The study takes a processual approach to offer an in-depth analysis of the interviewees’ social trajectories, socialization patterns, and real working conditions. Two profiles emerge from these case studies: teachers from working-class backgrounds who view their profession as a politically significant form of social advancement, and teachers who were politicized later through working in disadvantaged areas. The study demonstrates that while left-wing politicization persists, it is undergoing a transformation: it sometimes coexists with a managerial vision of the profession and can lead to disenchantment as a result of growing fragmentation within the professional sphere.